The Effect of Formaldehyde Disinfectant on Compressive Strength of Dental Stone (Type IV) - Musab Mohamed Ibrahim; Munther Najeeb Kazanji; Salwa Hachim Mohammed (University of Mosul, College of Dentistry, 2016)
Aims: The purpose of this study is to evaluate the effect of 2% formaldehyde on compressive strength of dental stone (type IV), and to evaluate its antibacterial effect. Materials and methods: To study the effect of 2% formaldehyde on compressive strength of dental stone (type IV), ten samples of stone were prepared in cylindrical blocks and divided into two groups, each group contain of (5) samples. First group composed of stone and distilled water as (control group) and the second group composed of stone and (2%) formaldehyde solution. after (1h) the samples were tested for compressive strength using digital compression machine(ALFA Company, Turkey).To study the bacterial effect of formaldehyde 60 stone discs prepared and mixed with formaldehyde 2% divided into 12 group (each group consist of 5 discs) and stored for different intervals between 1-12 days, antibacterial effect against salivary sample for each interval day using disc diffusion test. Results: The statistical analysis of data by analysis of t-test reveals significant different in compressive strength between control group and stone-2% formaldehyde group at (P<0.05). The result showed that second group which contains 2%formaldehydehad higher values compared with control group. Also the results showed that the antibacterial effect of stone-formaldehyde discs continued till 12thday. Conclusions: Adding 2% formaldehyde as chemical disinfectant to dental stone increase the compressive strength in addition of the antibacterial activity of stone - formaldehyde disc continued till 12th day.